Cerebral arteriopathy associated with heterozygous variants in the casitas B-lineage lymphoma gene. (August 2020) - Hong, Ying; Keylock, Annette; Jensen, Barbara; Jacques, Thomas S.; Ogunbiyi, Olumide; Omoyinmi, Ebun; Saunders, Dawn; Mallick, Andrew A.; Tooley, Madeleine; Newbury-Ecob, Ruth; Rankin, Julia; Williams, Hywel J.; et al.
Abstract : Objective: To report a series of patients with cerebral arteriopathy associated with heterozygous variants in the casitas B-lineage lymphoma ( CBL ) gene and examine the functional role of the identified mutant Cbl protein. We hypothesized that mutated Cbl fails to act as a negative regulator of the RAS-mitogen-activated protein kinases (MAPK) signaling pathway, resulting in enhanced vascular fibroblast proliferation and migration and enhanced angiogenesis and collateral vessel formation. Methods: We performed whole-exome sequencing in 11 separate families referred to Great Ormond Street Hospital, London, with suspected genetic cause for clinical presentation with severe progressive cerebral arteriopathy. Results: We identified heterozygous variants in the CBL gene in 5 affected cases from 3 families. We show that impaired CBL -mediated degradation of cell surface tyrosine kinase receptors and dysregulated intracellular signaling through the RAS-MAPK pathway contribute to the pathogenesis of the observed arteriopathy. Mutated CBL failed to control the angiogenic signal relay of vascular endothelial growth factor receptor 2, leading to prolonged tyrosine kinase signaling, thus driving angiogenesis and collateral vessel formation. Mutant Cbl promoted myofibroblast migration and proliferation contributing to vascular occlusive disease; these effects were abrogated following treatment with a RAF-RAS-MAPK pathway inhibitor. Conclusions: We provide a possible mechanism for the arteriopathy associated with heterozygous CBL variants. Identification of the key role for the RAS-MAPK pathway in CBL -mediated cerebral arteriopathy could facilitate identification of novel or repurposed druggable targets for treating these patients and may also provide therapeutic clues for other cerebral arteriopathies.